2021
DOI: 10.1172/jci.insight.147063
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of intrathecal gadobutrol for assessment of cerebrospinal fluid tracer clearance to blood

Abstract: Background. Methodology for estimation of cerebrospinal fluid (CSF) tracer clearance could have wide clinical application in predicting excretion of intrathecal drugs and metabolic solutes from brain metabolism, and for diagnostic work-up of cerebrospinal fluid disturbances.Methods. The magnetic resonance imaging (MRI) contrast agent gadobutrol (Gadovist) was utilized as CSF tracer and injected into the lumbar CSF. Gadobutrol is contained outside blood vessels of the central nervous system (CNS) and is thus el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 66 publications
3
47
0
Order By: Relevance
“…Additionally, in vivo measurements in humans demonstrating trans-arachnoid molecular passage in the PSD region were conducted by introducing gadolinium contrast into the subarachnoid space via intrathecal injection [ 2 ], with subsequent T 1 -weighted imaging detailing contrast progression to the PSD. Following this finding, a more recent study using intrathecal gadobutrol injection assessed the clearance of CSF in humans over an extended time period of 48 h in adults with CSF leakage disorders [ 29 ]. This study observed an increase of the CSF tracer in the blood after approximately 10 h, yet a delayed increase in the tracer in extracranial lymphatic structures, which peaked at approximately 24 h post-injection.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in vivo measurements in humans demonstrating trans-arachnoid molecular passage in the PSD region were conducted by introducing gadolinium contrast into the subarachnoid space via intrathecal injection [ 2 ], with subsequent T 1 -weighted imaging detailing contrast progression to the PSD. Following this finding, a more recent study using intrathecal gadobutrol injection assessed the clearance of CSF in humans over an extended time period of 48 h in adults with CSF leakage disorders [ 29 ]. This study observed an increase of the CSF tracer in the blood after approximately 10 h, yet a delayed increase in the tracer in extracranial lymphatic structures, which peaked at approximately 24 h post-injection.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to CSF clearance of neurotoxic solutes involved in neurodegeneration, human data suggest CSF resorption capacity at the upper brain convexities plays a minor role, as tracer clearance from CSF peaks in blood far earlier than peak levels are reached in CSF underneath the skull vertex. 37 The relative importance of meningeal lymphatic vessels for egress of neurotoxic metabolites in neurodegenerative disease needs to be further studied. Experimental data have shown that impaired meningeal lymphatic function caused reduced paravascular influx of macromolecules into the brain, and reduced efflux from the interstitial space.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Eide et al [ 215 ] have reported on concentrations of gadobutrol in brain and blood after injection into lumbar CSF. “The peak concentration in blood (at about 10 hrs) preceded by far peak tracer enhancement at MRI in extra-cranial lymphatic structures (at about 24 hrs) as shown in previous studies, indicating a major role of the spinal canal in CSF clearance capacity.“ This emphasizes yet again that distribution of markers for extracellular fluids by CSF is an important factor in their delivery to the brain parenchyma.…”
mentioning
confidence: 99%